Succession of Ethnic Beliefs : Mae Bot Nora Dance to Mae Bot Yai Dance - et. al., Manissa Vasinarom, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article aims to study the succession of ethnic beliefs : the case study of Mae Bot Nora Dance and Mae Bot Yai Dance. The scope of the study focuses on the Three Seals Law by studying from documentation, interviews, and observations. The results showed that, the dance was a tool for spreading beliefs, religion, and showing ethnic identity, which can be seen in the literature and performing arts. It is found that Mae Bot Nora Dance is influent by beliefs in spirits, Buddhism, and Brahman, which were the major beliefs among local people of Thailand. It’s developed continue in Thonburi Era and Rattanakosin Era by recording in poem’s Posture of Thai Classical Dance text for practice and performance. until 1944 thatLuang Wichitwatakan of the Fine Arts Department has restored the poem on the dance and applied it in the performance of Suriyagupta, which later became the basic practice dance in the Thai dance course. The lyric presents the succession of beliefs in spirits, Buddhism, and Brahman, which rooted deep in Thai society and culture, along with the combination of ethnic cultures that were recorded in the Three Seals Law.In summary, the Mae Bot dance can be seen as a record of the history, beliefs, and ethnicities of Thai society in a form of performing arts and in the persons who keep this practice in the education system and in performances that are still ongoing today.